PENGARUH DUKUNGAN ORGANISASI DAN SIKAP KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. PRIMA UTAMA - Muhammad Eirsyah Nusa Putra; Anoesyirwan Moeins; Kasmir Kasmir (MAGMA : JURNAL MAGISTER MANAJEMEN, 2019)
This study aims to determine and analyze the influence of organizational support and work attitudes on work productivity of PT. Prime Prima. The research method used in this study is a survey method with a correlational approach, which is a research method designed to obtain information about the relationships between different variables in one population. The instrument used in this study consisted of questionnaires for each variable that was valid and reliable. The results of the study show that 1) Organizational support has a positive and significant effect on employee work productivity, meaning that the higher the organizational support provided, the more work productivity of employees will increase. 2) An effective work attitude has a positive and significant effect on employee work productivity, meaning that the better the work attitude that employees have, the employee's work productivity will increase. 3) Organizational support and work attitudes together have a positive and significant effect on employee work productivity, meaning that the higher the organization's support and the better the work attitude that is owned, then the work productivity of employees will increase.